2011
DOI: 10.1002/ijc.25756
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine depletes regulatory T‐cells in human and mice and enhances triggering of vaccine‐specific cytotoxic T‐cells

Abstract: Particle-mediated epidermal delivery (PMED) is a potent genetic vaccination method. However, a recent report found PMED only poorly and infrequently triggered antigen-specific cytotoxic T-cells in cancer patients. Here, we show that injection of the chemotherapeutic drug Gemcitabine in mice results in improvement of the efficacy of subsequent PMED vaccination against NY-ESO-1. We found in mice and in cancer patients that administration of Gemcitabine induces a transient reduction in the percentage of regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 26 publications
6
45
0
Order By: Relevance
“…186). In mice, CD8 + responses elicited by HLA-A2-restricted peptides from auto-immunogenic cancer-testis antigen 1 (NY-ESO-1; also known as CTAG1) can be improved by the administration of gemcitabine 187 , in line with the immunostimulatory effects observed in patients treated with this nucleoside analogue (as mentioned above) 68,71,187 .…”
Section: Immunochemotherapymentioning
confidence: 73%
“…186). In mice, CD8 + responses elicited by HLA-A2-restricted peptides from auto-immunogenic cancer-testis antigen 1 (NY-ESO-1; also known as CTAG1) can be improved by the administration of gemcitabine 187 , in line with the immunostimulatory effects observed in patients treated with this nucleoside analogue (as mentioned above) 68,71,187 .…”
Section: Immunochemotherapymentioning
confidence: 73%
“…Also other chemotherapeutic compounds may affect Tregs and immune suppressive myeloid cells. Gemcitabine is known to reduce both Tregs and MDSCs in mice and in patients with ovarian cancer [53,54,80,100,101]. A selective decrease in MDSCs was also observed after treatment with 5-fluorouracil (5-FU) [102].…”
Section: Administration Of Chemotherapy Before Vaccination Alleviatesmentioning
confidence: 99%
“…In this work we demonstrated that the chemotherapeutic gem applied alone in vitro to splenocytesobtained from PDAC-bearing mice reduced the frequency of Treg in the culture. This effect was not present in case of splenocytes from healthy mice and thus, seems to be tumor specificThis can be explained by the fact that gem showed its cytotoxic activity merely on the high proliferative Treg which is present in tumor bearing host [22,27].This result corroborates in vivo data showing that gem, applied conventionally or in low dose, successfully depletes Treg from tumors and spleens from-tumor bearing hosts including PDAC, and in turn enhances the anti-tumor immunity [22,28,29]). However, approaches aiming to deplete Treg in cancer should be recognized with caution, since these may cause some adverse effects [30].…”
Section: Discussionmentioning
confidence: 67%